Optimalisasi Simas (Sistem Informasi Masjid) oleh Seksi Bimas Islam dalam Meningkatkan Efektivitas Pendataan Masjid di Kantor Kementerian Agama Kabupaten Lumajang - Himmah, Elok Faiqotul; Al Ahsani, Nasirudin (Maddah: Journal of Advanced Da'wah Management Research, 2024)
The main issue in mosque maintenance is the need for funding. In Lumajang, several areas in Jatiroto subdistrict and its surroundings frequently conduct fundraising on the highways to expedite the construction or rehabilitation of mosques. Another alternative is to obtain operational assistance from the government by integrating or registering with SIMAS. Optimizing SIMAS is important to support the management and dissemination of mosque-related information. The focus of the research is: 1) How does the Islamic Guidance Section optimize SIMAS? 2) How is the effectiveness of mosque data collection improved at the Lumajang Office of Religious Affairs? This study uses a qualitative research method with a descriptive research type. The research subjects are selected using purposive sampling. Data collection techniques include interviews, observation, and documentation. Data analysis techniques follow the Miles and Huberman model. Data validity is ensured using source and technique triangulation. The results of this study are as follows: In optimizing SIMAS, 1) The Islamic Guidance Section synergizes with the Village Government, KUA, and DMI. 2) Provides accurate and easily accessible mosque information to the public. 3) Offers friendly and informative services. There has been an increase in the effectiveness of mosque or prayer room data collection. As of May 2023, approximately 1,382 mosques and around 3,422 prayer rooms in Lumajang have been recorded in SIMAS, complete with addresses, land area, building area, Google Maps locations, and the number of mosque staff.